Exergy analysis of day light using fuzzy logic controllers of Jordanian commercial buildings - Ali M Baniyounes; Yazeed Ghadi; Mazen Alnabulsi (International Journal of Power Electronics and Drive Systems (IJPEDS), 2020)
Saving energy and greenhouse gas emissions in commercial buildings become a very serious request of buildings’ designers and engineering crew. The goal behind the current research is to high light and demonstrate the outcome of utilizing advance and intelligent building management system (IBMS) based in utilizing a fuzzy logic controller that allows the usage and the control of natural light (day light). The fuzzy logic controller (FLC) was sat to control the buildings dimming system while utilizing natural light which normally allows to add outdoors illuminance into the inside ones. This control system is significant mean technique that can be used in intelligent buildings commercial buildings, hence energy savings and consequently, greenhouse gas emissions reduction. The proposed control system relies on enumerating the outdoor and the indoor illuminance and allowing some add-on controllers in order to put into effect a photometric computer that capable of comparing and tasking decisions to regulate rooms lighting fixtures. The article also demonstrates energy savings using this technique and then suggest proper markets for using this controlling system whether during the buildings’ design stage, existing commercial buildings.